2022
DOI: 10.1111/ans.18032
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open groin hernia repair in older adults: a systematic review and meta‐analysis

Abstract: Background: Groin hernia repair is a common surgical procedure and includes both open and laparoscopic techniques. Studies comparing outcomes of laparoscopic versus open groin hernia repair specifically in the geriatric population are lacking. This study compares the outcomes of laparoscopic versus open groin hernia repair techniques in older adults. Methods: A literature search was conducted in each of the five selected databases up till June 2021: PubMed (MEDLINE), EMBASE, CINAHL, Cochrane and PsychInfo (OVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Traditionally, open and laparoscopic techniques have been the primary methods for inguinal hernia repair [ 27 ]. Laparoscopic hernia repair has gained significant attention from surgeons and patient preference due to its advantages, including reduced trauma, lower infection rates, and shorter postoperative recovery times [ 28 ]. The introduction of robotic surgical systems has greatly advanced the field of minimally invasive surgery [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, open and laparoscopic techniques have been the primary methods for inguinal hernia repair [ 27 ]. Laparoscopic hernia repair has gained significant attention from surgeons and patient preference due to its advantages, including reduced trauma, lower infection rates, and shorter postoperative recovery times [ 28 ]. The introduction of robotic surgical systems has greatly advanced the field of minimally invasive surgery [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was no mortality in both groups. As described, compared to OIHR (LTFR), LIHR has the advantages of lower incidence of hematoma, lower rates of seroma, less postoperative pain, faster recovery and less wound infection rate [4,29] , which are also applicable to elderly patients [11,12] . After PSM, there were no signi cant differences in baseline between LIHR and OIHR groups (Table 1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…Although no prospective studies have reported the correlation between age, surgical methods (LIHR and OIHR), and surgical outcomes. A retrospective study found that in the treatment of inguinal hernia repair in elderly patients, LIHR also showed similar advantages [11] .…”
Section: Introductionmentioning
confidence: 99%
“…The perspective 1 also raises the important topic of the cost of deliver in surgical services, in particular the cost of laparoscopic inguinal herniorrhaphy, given that open and laparoscopic approaches have similar outcomes 3 . This edition of the journal also publishes two articles showing not dis‐similar outcomes in the elderly 4 and in infants 5 . Cost is not only influenced by the method of repair (open, laparoscopic or robotic) and equipment used, but also by the model of care, especially whether the procedure involves a day stay or overnight stay.…”
mentioning
confidence: 99%
“…Safety, quality of care and patient experience are not compromised when appropriate patients are selected and clear expectations of same-day discharge are set and agreed. The outcomes of hernia surgery are similar regardless of the approach used, [3][4][5][6] so surgeons should feel free to choose an approach, whether open or laparoscopic, based on their experience and which can be performed safely, aiming to achieve the best outcome for their patients.…”
mentioning
confidence: 99%